Environmental Stress in Chickens and the Potential Effectiveness of Dietary Vitamin Supplementation - Akinyemi, Fisayo; Adewole, Deborah (Frontiers in Animal Science, 2021)
Environmental stressors can promote the vulnerability of animals to infections; it is therefore, essential to understand how stressors affect the immune system, the adaptive capacity of animals to respond, and effective techniques in managing stress. This review highlights scientific evidence regarding environmental stress challenge models and the potential effectiveness of vitamin supplementation. The major environmental stressors discussed are heat and cold stress, feed restriction, stocking density, and pollutants. Much work has been done to identify the effects of environmental stress in broilers and layers, while few involved other types of poultry. Studies indicated that chickens' performance, health, and welfare are compromised when challenged with environmental stress. These stressors result in physiological alterations, behavioral changes, decreased egg and meat quality, tissue and intestinal damage, and high mortalities. The application of vitamins with other nutritional approaches can help in combating these environmental stressors in chickens. Poultry birds do not synthesize sufficient vitamins during stressful periods. It is therefore suggested that chicken diets are supplemented with vitamins when subjected to environmental stress. Combination of vitamins are considered more efficient than the use of individual vitamins in alleviating environmental stress in chickens.